(Ab)Normal Returns in an Emerging Stock Market: International Investor Perspective. Issue 12 (26th September 2019) - Roszkowska, Paulina; Langer, Lukasz K.
ABSTRACT: This article studies the comparative attractiveness of public equity investments in the Polish (emerging) and in the U.S. (advanced) stock markets in the years 2000–2013. Through an original implementation strategy based on several one- and multifactor asset pricing models (APMs), we find that the potential for "beating the market" in the form of abnormal profits is higher in the Polish stock market, specifically related to size and profitability anomalies. The Fama–French five-factor model fares best in an international setting and yields additional monthly abnormal returns of 0.19 pp. An international investor should apply local, rather than global, risk factors to properly assess relative abnormal investment opportunities between markets.